The trade-off between customer and technology orientations: impact on innovation capabilities and export performance - Hortinha, P. (2015)
Technological exporters are constantly challenged by the trade-off between two types of strategic orientations: customer and technology. Nonetheless, research directly addressing this topic is scarce, and few recommendations exist about the best orientation to emphasize. Using two respondents in the same firm, the export manager and the research-anddevelopment manager, the authors find that customer orientation is as important as technological orientation in the development of exploratory innovation capabilities. However, when past performance is poor, customer orientation has a greater role. Exporters with poor past performance may achieve higher export performance levels by focusing more on customers than on technology. Conversely, firms performing well may risk export performance if they ignore technology orientation. These firms also need to maintain high levels of customer orientation